ANALYSE ET MODÉLISATION DE LA VULNÉRABILITÉ AUX MALADIES À TRANSMISSION HYDRIQUE DANS L’ESPACE URBAIN DE LA VILLE DE BATNA – NORD-EST ALGERIEN - BAZIZ NAFISSA; KALLA MAHDI; DRIDI HADDA; BOUTRID MOHAMED LAMINE (Revue Roumaine de Géographie)
Analysis and modelling of vulnerability to disease transmission water in the city of Batna – North- Eastern Algeria. In a semi-arid area the scarcity of water resources, including those for domestic consumption is often associated with the problem of potability, given their physical-chemical and bacteriological characteristics. The city of Batna, Algeria’s fifth largest city, has to cope with the quality of drinking water from a microbiological point of view, since there are many cases of infiltration of sewage into the water supply network (cross- connection). The environmental situation presents a real danger to public health and can cause epidemics difficult to contain. The numerous epidemic outbreaks observed in the past, along with more recent ones, suggest that drinking water could significantly contribute to endemic diseases. Indeed, the results of the recent bacteriological analyses made by us throughout the water cycle from source to tap via the network, show the continuing deterioration of the bacteriological quality of the water supplied to the city of Batna. The results confirmed our assumptions about the quality of the management of this resource and we showed how the Batnean urban space is marred by the inconsistency of both urban fabric and the associated networks. To estimate and spatialize the level of risk, we rely on a method for assessing vulnerability by digital index coupled with a Geographic Information System (GIS). Several methods have been developed for the assessment of vulnerability to pollution, among these the DRASTIC method, mostly used worldwide, has been identified as one of the vulnerability methods specific to appraising groundwater pollution. In this article we present a method for estimating the risk of vulnerability to waterborne diseases (WD) in a middle town of north-eastern Algeria. This method can be applied to any drinking water distribution network, taking into account the five parameters influencing vulnerability (outdated networks, unplanned urbanization, type and quality of materials behaviour, population density, and lack of water resources). Synthesis maps, spatializing these parameters enable visualization of the main areas at risk of water supply contamination in the city. The results should contribute to the protection of vulnerable areas and WD control in an urban zone and will be used to develop concerted urban development master plans.